2020
DOI: 10.1002/nme.6338
|View full text |Cite
|
Sign up to set email alerts
|

Finite element model updating using crow search algorithm with Levy flight

Abstract: Summary The accuracy of the finite element model is essential for fatigue analysis and vibration of a flexible body. This paper presents a finite element model updating (FEMU) algorithm based on crows search algorithm incorporated with Levy flight (LFCSA). The proposed algorithm is tested on the updating of two different cases: a simple structure (beam) and a complex structure (gearbox housing). To verify the performance of LFCSA, two optimization algorithm, which is the standard CSA and the particle swarm opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Figures 13 and 21 show that GWO converges faster than IFCSA in the middle of the iteration, but GWO will fall into the local optimum, and IFCSA can jump out of the local optimum to get a better solution. It can be seen from Figures 11,15,17, and 23 that the convergence speed and optimization accuracy of IFCSA are better than those of other algorithms. As can be seen from Figures 12,14,16,18,20,22, and 24, the performance of IFCSA algorithm is very stable.…”
Section: Comparative Experiments Of Different Intelligent Algorithms 431 High-dimensional Unimodal Function Test Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Figures 13 and 21 show that GWO converges faster than IFCSA in the middle of the iteration, but GWO will fall into the local optimum, and IFCSA can jump out of the local optimum to get a better solution. It can be seen from Figures 11,15,17, and 23 that the convergence speed and optimization accuracy of IFCSA are better than those of other algorithms. As can be seen from Figures 12,14,16,18,20,22, and 24, the performance of IFCSA algorithm is very stable.…”
Section: Comparative Experiments Of Different Intelligent Algorithms 431 High-dimensional Unimodal Function Test Resultsmentioning
confidence: 93%
“…One is to analyze and improve the parameters of the standard crow search algorithm, and the other is to integrate it with other intelligent algorithms to make up for the shortcomings of crow search algorithm. For the first kind of improvement, Wu et al proposed a crow search algorithm incorporated in Levy flight (LFCSA) [17] and applied it to update the finite element model. e chaotic sequence was used to initialize the population, so that the particles were evenly distributed in the solution space and the diversity of the population was increased.…”
Section: Introductionmentioning
confidence: 99%
“…3) Lévy flight & Opposition-based CSA Wu et al [102] introduced a novel approach of CSA named CCSA, in which an Lévy flight was used. The novel algo-rithm was tested on two different models: a simple structure (beam) and a complex structure.…”
Section: ) Modified Csamentioning
confidence: 99%
“…Previous studies [17][18][19] have shown that the wheel polygonization will lead to a surge in vibration response of various components of the vehicle. Wu et al [20,21] used an intelligent algorithm to improve the accuracy of the gearbox model and studied the influence of harmonic traction torque on the vibration and stress of the gearbox. Huang et al [22] established a dynamic model of a high-speed train and a finite element model of the gearbox housing and analyzed the influence of internal excitation (the periodic variation of meshing stiffness) and external excitation (rail excitation, harmonic traction torque).…”
Section: Introductionmentioning
confidence: 99%